Enhancement in the critical current density of BaTiO3-doped YBCO films by low-energy (60 keV) proton irradiation. (23rd February 2021) - Huang, Daxing; Gu, Hongwei; Shang, Hongjing; Li, Taiguang; Xie, Bowei; Zou, Qi; Chen, Di; Chu, Wei-kan; Ding, Fazhu
Abstract: Although YBa2 Cu3 O72212δ (YBCO) is one of the most promising superconducting materials for power applications, the fabrication of low-cost coated conductors with the high in-field performance remains challenging. Here, we report an efficient mixed-pinning landscape for enhancing the in-field performance of BaTiO3 (BTO)-doped YBCO films by low-energy (60 keV) proton irradiation. The smaller (2–4 nm), weaker but perhaps denser pinning sites have been successfully introduced by irradiation, which can form a mixed-pinning landscape with pre-doped BTO precipitates (5–15 nm), leading to the increased vortex pinning. In this case, the critical current density ( J c ) of YBCO films increases significantly, especially at low temperature and high magnetic field, and it increases three times near 6 T at 20 K when the irradiation dose is 1 × 10 15 proton cm −2 . Additionally, the c -axis length ( c -parameter) of YBCO increases with the increase of irradiation dose, which indicates the decreasing oxygen content due to the excessive irradiation, thereby the reduction in critical transition temperature ( T c ). Employing low irradiation energy is beneficial for protons to stop inside YBCO film and thereby induces higher density defects when applying low doses. This fabrication technique is a practicable post-production solution to improve the in-field performance of nanoparticle-doped YBCO films.